Exploring the impact of organisational, technological and relational contingencies on innovation speed in the light of open innovation. Issue 7 (8th August 2020) - Milan, Evita; Ulrich, Frank; Faria, Lourenco G.D.; Li-Ying, Jason
ABSTRACT: Striving for competitive advantage pushes firms to innovate at a high speed along innovation contingencies and resource limitations they face. Yet, little is known about how management of contingencies such as absorptive capacity or technology radicalness can impact the innovation speed of firms. In this explorative study, we provide new empirical evidence to the innovation speed literature. We examine to what extent innovation speed is affected by organisational, technological, and relational contingencies that preoccupy firms with open innovation practices. Taking the firm perspective, we track innovation timeline and emphasise the complex trade-offs that firms encounter while innovating. Our results show that many of the contingencies, emphasised by the literature promoting innovation, could slow down its speed. Thus, strengthening competitiveness by accommodating contingencies can hinder time-critical adaptations. Furthermore, we find that innovation assets and capabilities can become liabilities for technologically innovative firms.